Keperluan program pascapembebasan dan jagaan lanjutan berasaskan komuniti untuk bekas banduan / Mohd Alif Jasni - Mohd Alif , Jasni (2018)
Insufficiency of aftercare situates former prisoners at high risk of recidivism. Their tendency to repeating criminal activity resulted from various factors that could influence them in the ongoing recovery process. This study attempts to identifying risks and existing protective factors in the social environment of the former prisoners that could affect their decision either repeat or refrain themselves from undesirable behaviour towards criminal activities. Their choices would determine changes in their life afterwards whether turn back as a criminalize or avoiding it. A qualitative study has been carried out in Kuala Lumpur among sixteen recidivists, and three demisters through a series of in-depth interviews. The analysis indicates that majority of the former prisoners have failed to reintegrate with the community as a whole. As a result, failing from being threaded equally in society leading them in contributing to recidivism. This study implemented the Age Graded Theory of Informal Social Control as the theoretical framework to understand changes that occurred during life occurrences or incidents of these former prisoners. Hence, this analysis has been preceded to the identification of various risk and protective factors that responding as contribution factors to their recidivate and desistance behaviour. Thus, inputs are vital for the establishment of a realistic community-based post-release and post rehabilitation programme that could facilitate the reintegration process of the former prisoners. As a conclusion, the exconvictors need to be observed in the community form time to time. Therefore, a post rehabilition programme should be one of the initiative in bringing ex-convictors back to normal functioning community and well blend in. In addition, post rehabilitation could help the former prisoners to reintegrate and become an obedient and law abiding citizen.